2021
DOI: 10.1093/rfs/hhab023
|View full text |Cite
|
Sign up to set email alerts
|

Do Index Funds Monitor?

Abstract: Passively managed index funds now hold over 30% of U.S. equity fund assets; this shift raises fundamental questions about monitoring and governance. We show that, relative to active funds, index funds are less effective monitors: (a) they are less likely to vote against firm management on contentious governance issues; (b) there is no evidence they engage effectively publicly or privately; and (c) they promote less board independence and worse pay-performance sensitivity at their portfolio companies. Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(39 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…In fact, large passive funds tend to exhibit a more "disciplinarian" attitude toward management (Bolton, Li, Ravina, and Rosenthal (2019))-and institutional common owners not only internalize governance externalities but also are more likely to vote against management (He, Huang, and Zhao (2019)). 10 There are, however, countervailing agency problems: Bebchuk and Hirst (2019) pointed out that index fund managers may not have incentives to monitor management (for evidence that index funds are less likely to vote against management than are active funds, see Brav, Jiang, Li, Pinnington (2019), Heath, Macciocchi, Michaely, andRinggenberg (2019)). Schmidt and Fahlenbrach (2017) showed that increased passive ownership impedes high-cost governance activities and increases 8 See Vives (2020) for an exposition of (a) the tension between market power and efficiency as an outcome of common ownership and (b) a parallel with debates in the 1960s and 1970s over the "structure-conductperformance" paradigm in the field of industrial organization.…”
Section: Empiricsmentioning
confidence: 99%
“…In fact, large passive funds tend to exhibit a more "disciplinarian" attitude toward management (Bolton, Li, Ravina, and Rosenthal (2019))-and institutional common owners not only internalize governance externalities but also are more likely to vote against management (He, Huang, and Zhao (2019)). 10 There are, however, countervailing agency problems: Bebchuk and Hirst (2019) pointed out that index fund managers may not have incentives to monitor management (for evidence that index funds are less likely to vote against management than are active funds, see Brav, Jiang, Li, Pinnington (2019), Heath, Macciocchi, Michaely, andRinggenberg (2019)). Schmidt and Fahlenbrach (2017) showed that increased passive ownership impedes high-cost governance activities and increases 8 See Vives (2020) for an exposition of (a) the tension between market power and efficiency as an outcome of common ownership and (b) a parallel with debates in the 1960s and 1970s over the "structure-conductperformance" paradigm in the field of industrial organization.…”
Section: Empiricsmentioning
confidence: 99%
“…Index funds seek to match the returns of a published index, so they have limited investment trading choices, potentially making engagement through avenues like voting a more meaningful way to influence a portfolio firm. Prior research provides mixed evidence on whether index funds act as monitors on governance issues (e.g., Appel et al 2016;Heath et al 2022). However, index ESG funds may be more likely to monitor firms on ES issues because they have publicly acknowledged their commitment to these issues through their investment criteria in the prospectus filed with the SEC.…”
Section: Securities and Exchange Commission 2021)mentioning
confidence: 99%
“…On the other hand, diversified shareholders may suffer from a hold-up problem: the benefits from monitoring are shared by all owners, but the costs are not, so there is a disincentive to engage. Additionally, institutional owners with primarily passive funds may charge lower fees for these funds, limiting the resources they have available for costly monitoring and engagement activities (Bebchuk et al 2017); this, too, may lead to less effective monitoring (Heath et al 2019).…”
Section: Prior Researchmentioning
confidence: 99%